License Plate Readers for Law Enforcement Opportunities and Obstacles - Gierlack, Keith (RAND Corporation, 2014)
Because license plate reader (LPR) technology is relatively new in the United States, opportunities and obstacles in its use in law enforcement are still under exploration. To examine issues about this technology, RAND conducted interviews with law enforcement personnel, police officers, and others responsible for procuring, maintaining, and operating the systems.